An Anthropological Approach to Understanding the Dynamics of Islamic Education in Multicultural Society - Yulinda; Rusmaeni Rusmaeni; Ade Andriani; Ruslan Ruslan; Nasaruddin Nasaruddin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to examine the role of anthropological approaches in understanding the dynamics of Islamic education within Indonesia’s multicultural context, particularly in relation to the rising issues of intolerance, exclusivism, and tensions rooted in socio cultural diversity. Using a library research design, the study analyzes contemporary scholarly works, policy documents, and recent empirical findings published in the last five years to explore how local variations in Islamic educational practices emerge across pesantren, madrasah, and public schools. The research further investigates how Islamic teachings are negotiated, adapted, and reinterpreted within diverse cultural settings, and how these processes shape students’ attitudes toward tolerance and inclusivity. The findings show that anthropological perspectives emphasizing culture, context, and everyday social practices provide essential insights for building Islamic education models that are more adaptive, inclusive, and socially grounded. The study concludes that incorporating anthropological analysis into Islamic education policy and practice can strengthen multicultural understanding and contribute to the development of more cohesive and harmonious learning environments within Indonesia’s plural society.